2021
DOI: 10.1038/s41598-021-96455-9
|View full text |Cite
|
Sign up to set email alerts
|

Middle–Late Triassic sedimentary provenance of the southern Junggar Basin and its link with the post-orogenic tectonic evolution of Central Asia

Abstract: Due to the unknown Triassic volcanism in the Junggar Basin, the Middle–Late Triassic sedimentary provenance in the southern Junggar Basin (SJB) has long been controversial. Detrital zircon grains from 13 samples of the Middle–Upper Triassic Xiaoquangou Group in the SJB were analyzed using zircon U–Pb geochronology to constrain the provenance of Triassic sedimentary rocks and to further understand their source-to-sink system. Comparison of detrital zircon U–Pb age distributions for 13 samples reveals that the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…For example, Zhang et al (2013Zhang et al ( , 2020 the northern Alxa region and suggested that this intracontinental deformation resulted from the far-field effect associated with the collision between the Eurasia and different indenters including the Bayan Har Terrane and Yangtz Craton during the Late Triassic. And the study of the Triassic sedimentary provenance in the southern Junggar Basin also suggested that the Late Triassic uplift of the Bogda Mountains resulted from the far field effect of the Qiangtang-Eurasia collision (Wang et al, 2021). Therefore, we proposed that the Late Triassic intracontinental deformation in the Tianshan range is more likely to be related to far-field effects.…”
Section: Potential Driving Force and Tectonic Evolutionmentioning
confidence: 79%
“…For example, Zhang et al (2013Zhang et al ( , 2020 the northern Alxa region and suggested that this intracontinental deformation resulted from the far-field effect associated with the collision between the Eurasia and different indenters including the Bayan Har Terrane and Yangtz Craton during the Late Triassic. And the study of the Triassic sedimentary provenance in the southern Junggar Basin also suggested that the Late Triassic uplift of the Bogda Mountains resulted from the far field effect of the Qiangtang-Eurasia collision (Wang et al, 2021). Therefore, we proposed that the Late Triassic intracontinental deformation in the Tianshan range is more likely to be related to far-field effects.…”
Section: Potential Driving Force and Tectonic Evolutionmentioning
confidence: 79%
“…Zircon crystallisation ages are reported in Table S2. Following previous authors (Baesso et al, 2021; Markwitz et al, 2017; Olierook et al, 2019; Philipp et al, 2021; Wang et al, 2021), ages with discordance >10% were discarded (n = 17). We used the 206 Pb/ 238 U age to date the zircons younger than 1.3 Ga and the 206 Pb/ 207 Pb age for the zircons older than 1.2 Ga, in agreement with Gehrels et al (2008).…”
Section: Resultsmentioning
confidence: 99%
“…Provenance analysis aims at locating the source areas of detrital sediments based on a wide range of petrological evidence (Boggs Jr, 2009). Over the past decade, provenance analysis of heavy minerals has emerged as a powerful tool for reconstructing the tectono‐sedimentary evolution of rift basins (Baesso et al, 2021; Hart et al, 2016; Olierook et al, 2019; Wang et al, 2021). So far, the scarcity of coarse detrital material precluded a provenance analysis of pre‐break‐up deposits of the Demerara Plateau.…”
Section: Introductionmentioning
confidence: 99%
“…From the detrital zircon age study of samples from the central TB, we found that multiple provenances supplied weathered source rocks, and due to the overlap of detrital zircon ages from the basin boundary mountains, there are multiple solutions, and the primary and secondary relationships of the source supply are difficult to determine. Thus, geochronology (J. Wang et al, 2021), palaeocurrents (Lin, 1994), petrology (Greene et al, 2005) and heavy minerals (J. Zhang et al, 2020) are further used in the study of some strata source‐to‐sink systems in the TS area. Here, we mainly focus on the application of heavy minerals collected from wells in Jurassic strata to further constrain the provenances (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, geochronology (J. Wang et al, 2021), palaeocurrents (Lin, 1994), petrology (Greene et al, 2005) and heavy minerals (J. Zhang et al, 2020) are further used in the study of some strata source-tosink systems in the TS area.…”
Section: Potential Sources Area Of Jurassic Rocks Constrained By Heav...mentioning
confidence: 99%